Karakteristik Sawi Hijau (Brassica rapa var parachinensis) yang Dihasilkan dari Aplikasi Bakteri Pemacu Pertumbuhan - Triani, I Gusti Ayu Lani; Gunam, Ida Bagus Wayan (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 1 (2022)DO - 10.24843/JITPA.2022.v07.i01.p08, 2022)
This study tries to use the roots of bamboo plants that grow in Bali as Plant Growth Promoting Rhizobacteria and applied to vegetable plants to see the physical characteristics of these vegetables. This study aims to determine the physical characteristics of greens mustard produced by using the application of growth-promoting bacteria derived from the roots of bamboo ( Bambusa maculata ). The characteristics of the greens mustard were compared with the use of commercial PGPR (products from Central Java farmers) and without the use of growth-promoting bacteria. Based on the results of the research on the physical characteristics of greens mustard ( Brassica rapa var parachinensis ) the results of the application of growth-promoting bacteria from bamboo roots obtained plant heights ranging from 39 cm, weight 34 – 44 g, number of leaves 9 – 12 pieces, texture 22.18 – 30.31 kg .m/sec 2 , brightness level 42.13 – 47.13 and total dissolved solids 4.4 – 5.1% brix, slightly different from the treatment without PGPR and commercial PGPR. For this reason, it is necessary to continue cultivation with growth-promoting bacteria derived from natural ingredients that grow in Bali, this is an effort towards environmentally friendly cultivation so that it is expected to get quality results and are safe for consumption.